A histopathological report of a 16-year-old male with peripheral pulmonary artery stenosis and Moyamoya disease with a homozygous RNF213 mutation. (2020) - Takahashi, Kei; Nakamura, Junichi; Sakiyama, Shinya; Nakaya, Toshitaka; Sato, Takahiro; Watanabe, Taku; Ohira, Hiroshi; Makita, Keishi; Tomaru, Utano; Ishizu, Akihiro; Tsujino, Ichizo
Abstract: Peripheral pulmonary artery stenosis (PPAS) is a rare pulmonary vasculopathy characterized by multiple stenoses and obstructions in the peripheral pulmonary arteries. PPAS often develops in children with congenital diseases such as Williams syndrome and Alagille syndrome; however, recent studies have reported PPAS cases in adults with Moyamoya disease (MMD). Recent genetic studies have demonstrated that ring finger protein 213 (RNF213) is a susceptibility gene for MMD. However, the pathophysiology of combined PPAS and MMD and the relationship between the two diseases remain largely unknown. Here we report a case of PPAS in a 16-year-old male, with a history of MMD, who died suddenly at 24. An autopsy was performed, and remarkable pathological changes were identified in the pulmonary arteries and in other arteries. Furthermore, genetic analysis revealed that the patient had a homozygous c.14576G > A (p.R4859K) mutation in RNF213. This is the first report to demonstrate the histopathology of systemic arteriopathy in a case with MMD and PPAS with a confirmed homozygous RNF213 mutation. We also review immunohistochemical data from the case and discuss how RNF213 mutation could have resulted in the observed vascular abnormalities.